A MIXED-METHOD STUDY TO ENHANCE FOOD SECURITY BY REDUCING POST-HARVEST WHEAT LOSSES IN PUNJAB, PAKISTAN: Food Security with emphasizing loss prevention - Manzoor, Adeela; Ahmad Maan, Ashfaq; Ahmad Khan, Izhar; Shahbaz, Babar (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: The major purpose of this study was to enhance food security by reducing wheat losses. Methodology: A mixed-method research was used for data collection. Six focus group discussions and six key-informant interviews were conducted to cover qualitative aspects while 400 face-to-face interviews were conducted. The study was conducted in three randomly selected districts of Punjab. Six tehsils, two from each district were further selected randomly. From each selected tehsils, four hundred farming households were selected through a proportionate sampling technique, and data were collected through an interview schedule. : For the qualitative aspect thematic analysis was used to analyze data. The quantitative data were analyzed through the statistical package for social sciences (SPSS) Main Findings: The result of the present study shows that majority of respondents having old age were doing wheat post-harvest activities and they have only a primary level of education. The farmers who have access to extension services had less level of losses rather than others. Qualitative results show that the farmers who are trained with techniques to manage post-harvest activities have fewer losses as compare to the farmers who are not trained. Applications of this study: It is concluded that hurdles regarding canal water, marketing, transportation, and practices of traditional methods for wheat storage lead to post-harvest losses as well. It is a sheer need of time to train the people (involved in postharvest management activities) to reduce the postharvest losses according to their needs.